The effects of international migration on native workers' unionization in Austria - José Ignacio Antón Pérez; René Böheim; Rudolf Winter-Ebmer (Johannes Kepler University Linz, Christian Doppler Laboratory Aging, Health and the Labor Market, 2016)
We analyze the effects of increased immigration of foreign workers on the unionization rates of native workers in Austrian firms over the period 2002-2012. Our results suggest that lower union density of natives' in firms with more foreign workers is driven not by natives leaving unions, but by the different composition of turnover depending on the share of foreigners in the firm.
Keywords: J51; J61; J63; 330; migration; unions; turnover; hiring